THE USE OF LITERARY TEXTS TO DEVELOP CULTURAL AND LANGUAGE SKILLS AND CULTURAL AWARENESS Case Study: First Year Secondary School Textbooks in Messaad, Djelfa - Guendouz ?Messaoud; Ben Redda ?Djamel (Faculty of Letters and Foreign Languages Department of English, 2018)
The present research is an attempt to examine the use of literary texts to develop language skills and cultural awareness of first-year secondary school teachers, pupils and textbook, of English, 'At the Crossroad'. This study provides an analysis of the literary texts used in the textbook, as well as an investigation of teachers' awareness of the importance of using literary texts in the ELT (English Language Teaching) classroom through a questionnaire. The findings of this research demonstrate, on the one hand, a lack of positive exploitation of the benefits that literary texts can provide, and on the other hand, a lack of understanding among teachers of how to put literary texts to good use. Although the majority of secondary school teachers show a significant amount of awareness of the importance of using authentic literary texts, many of them require training in terms of picking the right literary texts and applying the right techniques to use them in the classrooms.